First records of long-legged flies (Diptera, Dolichopodidae) from Fars Province of Iran - Rezaei, S.; Grichanov, I. Ya.; Fallahzadeh, M. (Acta Biologica Sibirica, 2019)
This paper provides data on distribution of 9 long-legged fly species (Diptera, Brachycera, Dolichopodidae) belonging to 6 genera from Fars province, southern Iran. Four species, Asyndetus albifrons Loew, 1869, Asyndetus chaetifemoratus Parent, 1925, Medetera media Parent, 1925 and Sciapus adumbratus (Becker, 1902) are newly added to the Iranian insect fauna. In addition, available information for each species and comments on geographical distribution and taxonomy are also included.